DIABETIC KETOACIDEOSIS (DKA)-ASSOCIATED HEMICHOREA-HEMIBALLISM IN TYPE 2 DIABETES MELLITUS: AN UNCOMMON EVOLVING CONDITION FROM NON-KETOTIC HYPERGLYCEMIA TO DIABETIC KETOACIDOSIS - Thewjitcharoen, Yotsapon; Tongpoo, Nopparath; Veerasomboonsin, Veekij; Anutakulnatee, Tawee; Nakasatien, Soontaree; Krittiyawong, Sirinate; Himathongkam, Thep (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION Non-ketotic hyperglycemic hemichorea-hemiballism is a well-known phenomenon in elderly patients who have poorly controlled type 2 diabetes mellitus (T2DM), typically in female Asians. Its occurrence as an evolving condition from non-ketotic hyperglycemia to diabetic ketoacidosis (DKA) is extremely uncommon. CASE A 79-year-old Thai woman with T2DM was transferred from a provincial hospital to our intensive care unit with urosepsis and abnormal movements in right arm and leg for 4 days. At the referral hospital, she had been admitted with uncontrolled hyperglycemia with the similar less severe right-sided abnormal movements. A plain cranial CT revealed bilateral basal ganglion calcification without hypodense lesions. However, she was diagnosed with lacunar stroke and abnormal movements subsided with supportive treatments. Two months later, she returned to the hospital with lethargy and abrupt onset of rightsided involuntary movements. She was diagnosed with non-ketotic hyperglycemia with a plasma glucose level of 343 mg/dL and glycated hemoglobin of 9.8%. Supportive treatment with subcutaneous insulin was given but her abnormal movements worsened. On arrival at our hospital, urosepsis-precipitated DKA was diagnosed with rightsided abnormal movements that were compatible with hemichorea-hemiballism. The non-contrast cranial CT revealed slightly increased attenuation at left putamen. DKA-associated hemichorea-hemiballism was suspected and her condition slowly improved over 2 months after resolution of DKA with strict glycemic control and antidopaminergic medications. CONCLUSION This case highlights the importance of considering: diabetic Striatophaty or hyperglycemia-induced hemichorea hemiballisim syndrome could be developed in both nonketotic and ketotic conditions.